2010
DOI: 10.4049/jimmunol.0902797
|View full text |Cite
|
Sign up to set email alerts
|

Dual Effects of TRAIL in Suppression of Autoimmunity: The Inhibition of Th1 Cells and the Promotion of Regulatory T Cells

Abstract: TRAIL is known to play a pivotal role in the inhibition of autoimmune disease. We previously demonstrated that administration of dendritic cells engineered to express TRAIL and myelin-oligodendrocyte glycoprotein reduced the severity of experimental autoimmune encephalomyelitis and suggested that CD4+CD25+ regulatory T cells (Tregs) were involved in mediating this preventive effect. In the current study, we investigated the effect of TRAIL on Tregs, as well as conventional T cells, using TRAIL-deficient mice. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
92
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(98 citation statements)
references
References 38 publications
4
92
0
2
Order By: Relevance
“…5D, Table I), which was recently localized mainly to the syncytiotrophoblast within the placenta (28). TRAIL was shown to preferentially expand the Treg population and to inhibit expansion of the non-Treg cell pool in a mouse model (29). Because we observed that PE CM significantly reduced the viability of unstimulated CD4 + T cells (Fig.…”
Section: Soluble Placental Factors Preferentially Induce Foxp3mentioning
confidence: 67%
See 2 more Smart Citations
“…5D, Table I), which was recently localized mainly to the syncytiotrophoblast within the placenta (28). TRAIL was shown to preferentially expand the Treg population and to inhibit expansion of the non-Treg cell pool in a mouse model (29). Because we observed that PE CM significantly reduced the viability of unstimulated CD4 + T cells (Fig.…”
Section: Soluble Placental Factors Preferentially Induce Foxp3mentioning
confidence: 67%
“…In contrast, IL-10 was recently reported to upregulate the antiapoptotic Bcl-2 specifically in Tregs, but not in conventional T cells, suggesting a mechanism for IL-10-driven maternal Treg expansion during pregnancy (54). Similarly, the apoptosis-inducing factor TRAIL was shown to expand the Treg pool and to inhibit the expansion of non-Tregs (29). Thus, both IL-10 and TRAIL could increase the proportion of Tregs by preferentially promoting the survival of already existing Tregs.…”
Section: Foxp3mentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, blocking both TNF and OX40L in ins-HA mice did not fully inhibit the Teff→Treg boost (data not shown), suggesting that other molecules were involved. Some of them may belong to the TNFR family, such as death receptor 3, death receptor 5, or glucocorticoid-induced TNFR family-related protein because these molecules are able to promote Treg cell expansion (35)(36)(37)(38)(39). Thus, molecular mechanisms of the Teff→ Treg boost are diverse and differ depending on the tissue and the type of inflammation.…”
Section: Molecular Mechanisms Of the Teff→treg Boostmentioning
confidence: 99%
“…6C-E (Chen et al, 2003;Rao et al, 2005). In contrast, the apoptosis-inducing factor TRAIL may promote the preferential expansion of an already existing Treg cell population while inhibiting expansion of non-Treg cells, as shown in a mouse model (Ikeda et al, 2010). IL-10 may also promote the preferential survival of Treg cells by specifically upregulating the anti-apoptotic Bcl-2 in Treg cells but not in conventional T cells (Santner-Nanan et al, 2013).…”
Section: Factors Involved In the Expansion Of Treg Cellsmentioning
confidence: 99%